Oh say can you fudge - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2015)
It's not Fourth of July on Mackinac Island without fireworks and fudge. The Historic McMurphy Hotel and Fudge Shop is supplying the treats--and Allie has hired Rodney Rivers, the biggest name in aerial displays, to create an unforgettable spectacle. Unfortunately, Allie finds him dead, covered with screaming chicken fireworks, just before the entire warehouse of pyrotechnics goes up in smoke. Is it arson or is it murder? Allie and her bichonpoo, Mal, must sift through the suspects until the killer is caught and the island can enjoy a star-spangled celebration.